Inorganic constituents in barks of Abies bornmulleriana and Castanea sativa - Hafizoglu, Harzemsah; SivriKaya, Hüseyin; Bacak, Latife; Sivrikaya, Hüseyin (Springer, 2006)
Barks of Abies bornmulleriana and Castanea sativa were investigated for inorganic constituents by flame atomic absorption spectrometer. 18 elements were detected in the barks of the two species. While Ca was found as the main constituent, 68.7% of the total elements in fir and 76.6% in chestnut, K, Mg, Al and Mn were seen as other predominating elements.
Keywords: Element